IMPLEMENTATION OF GREEN MARKETING STRATEGIES PT DAYA KHARISMA UTAMA (SUZUKI PONTIANAK) - Bima Julianto Pradana; Verdico Arief (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The decline in conventional car sales, coupled with the growing consumer preference for environmentally friendly vehicles, has encouraged automotive companies to adopt sustainable marketing strategies. This study examines the implementation, challenges, and solutions of green marketing strategies in the sales of the Suzuki New XL7 Alpha Hybrid at PT Daya Kharisma Utama (Suzuki Pontianak). A descriptive qualitative method was employed, using guided interviews and documentation to explore the company’s practices and experiences. The findings reveal that green marketing was implemented through canvassing programs, database utilization, digital marketing, exhibitions, electronic media, mediators and referrals, and showroom activities. Key challenges included budget limitations, suboptimal showroom locations, low consumer awareness, limited human resources, and gaps between planning and execution. To address these issues, the company optimized human resources, collaborated with external stakeholders, provided flexible test drives, enhanced internal education, and strengthened marketing communications. Overall, the study highlights the importance of cross-functional collaboration and continuous innovation in improving the effectiveness of green marketing strategies. The research contributes theoretically to the body of knowledge on green marketing in the automotive sector and offers practical implications for companies aiming to strengthen the competitiveness of environmentally friendly products.